The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/brainsci10090639
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse Inhibition of the Auditory Startle Reflex Assessment as a Hallmark of Brainstem Sensorimotor Gating Mechanisms

Abstract: When a low-salience stimulus of any type of sensory modality—auditory, visual, tactile—immediately precedes an unexpected startle-like stimulus, such as the acoustic startle reflex, the startle motor reaction becomes less pronounced or is even abolished. This phenomenon is known as prepulse inhibition (PPI), and it provides a quantitative measure of central processing by filtering out irrelevant stimuli. As PPI implies plasticity of a reflex and is related to automatic or attentional processes, depending on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 119 publications
(166 reference statements)
1
48
1
4
Order By: Relevance
“…PPI is the result of activity in the different brain circuits (brainstem, limbic, cortical, thalamic, strio-pallidary structures) and different synaptic mechanisms [ 36 , 37 , 38 ]. Some groups of patients with neuropsychiatric disorders display a deficiency of PPI.…”
Section: Introductionmentioning
confidence: 99%
“…PPI is the result of activity in the different brain circuits (brainstem, limbic, cortical, thalamic, strio-pallidary structures) and different synaptic mechanisms [ 36 , 37 , 38 ]. Some groups of patients with neuropsychiatric disorders display a deficiency of PPI.…”
Section: Introductionmentioning
confidence: 99%
“…Several murine studies have indicated that PPI is modulated by DA [ 52 , 53 , 54 , 55 , 56 ] and that schizophrenia is characterized by dopaminergic dysfunction in the striatum [ 57 , 58 ]. This is consistent with the PPI deficits we observed in DP groups, therefore suggesting altered dopaminergic functioning in these patients and that indirect DA agonists such as amphetamines and cocaine could decrease PPI.…”
Section: Discussionmentioning
confidence: 99%
“…The bilateral cerebellum, lingual gyrus and midbrain support emotion regulation, spatial memory, arousal and sensorimotor gating ( Gomez-Nieto et al, 2020 ; Hernaez-Goni et al, 2010 ). Of interest is the association of chronic abuse with blunted midbrain and lingual gyrus activity ( Table 3 , Supplemental Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is the association of chronic abuse with blunted midbrain and lingual gyrus activity ( Table 3 , Supplemental Figure 2 ). The midbrain supports arousal and sensorimotor gating functions ( Gomez-Nieto et al, 2020 ; Lang and Davis, 2006 ). Interestingly, we found blunted overall startle magnitude in post-institutionalized adopted adolescents versus non-adopted US born controls ( Quevedo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%